The effect of small games in modifying some behavioral manifestations of primary school students age group 9-10 years - Aboud, Hiyam Saadoon (International Journal of Psychosocial Rehabilitation, 2020)
Small games are a mirror that reflects the child's life, as it clearly shows his behaviors and behaviors and is a way to entertain him. Small games have a prominent role in building the child's personality by developing his athletic abilities and talents, in addition to modifying and changing his behavior to suit the needs of society.